Equipping oncologists for shared decision-making about palliative cancer treatment: Presenter(s): Danique Bos, Amsterdam UMC, Netherlands. (April 2023) - van Laarhoven, Hanneke; Ali, Rania; Tange, Dorien; Smets, Ellen
Abstract : Background: To promote shared decision-making (SDM) in palliative cancer care, we aimed to develop and evaluate an online blended learning for oncologists on SDM about palliative cancer treatment. In addition, the outcomes of the blended learning format were compared with those of a previously evaluated more intensive face-to-face format. Methods: The online blended learning was evaluated in a one-group pre-posttest design. Participating oncologists (n=17) engaged in an e-learning (1 hour) and online training session (3.5 hours). Simulated consultations and surveys were conducted before (T0) and after (T2) the blended learning; an additional survey was filled in after the e-learning (T1). SDM observed in the recorded consultations constituted the primary outcome, which was assessed by two raters using the OPTION12 and 4SDM. Secondary outcomes were the observed stages of SDM, conversation duration and decision made as well as oncologists' knowledge, clinical behavioural intention, satisfaction with the communication in the conversation and evaluation of the training. Data were analysed by Linear Mixed Models. Findings: The blended learning had a significant positive effect on the degree of observed SDM as assessed with the OPTION12 and the 4SDM (Cohen's d: 1.01 and 1.10, respectively). The individual steps of SDM, knowledge and satisfaction with the conversation increased significantly after training. Beliefs about capabilities (one factor of clinical behavioural intention) improved significantly; intention, social influence, moral norm and beliefs about consequences did not. The training was evaluated satisfactory by oncologists (average grade of 7.9/10) and the online modality was considered equal to a face-to-face modality in quality, usefulness and enjoyment. When compared with the face-to-face training evaluation data, the blended learning seemed less effective (Cohen's d: 0.37 (OPTION12) and 0.56 (4SDM)). Discussion: The results show that the blended learning can improve SDM by oncologists. Robust research designs are needed to strengthen the evidence on effective formats.